Diagnostic challenges and treatment options in patients with solitary fibrous tumor: A single-center observational study - Ozaniak, Andrej; Hladik, Pavel; Lischke, Robert; Strizova, Zuzana (Frontiers in Surgery, 2022)
Introduction: Solitary fibrous tumor (SFT) is an extremely rare disease with a high misdiagnosis rate and a potentially malignant biologic nature. We have collected and analysed data from 18 SFT patients to provide a deeper insight into this uncommon disease entity. Methods: In our study, a total number of 18 patients who had undergone surgery between April 2014 and December 2021 for the diagnosis of SFT were evaluated. The collected data for each patient included the location of the SFT, the pre-operative diagnosis, the definitive histological diagnosis, the presence of postoperative complications, the time of recurrence, the time of systemic progression, the type of treatment, and the survival rate. The median follow-up was 36 months. Results: In three patients, the pre-operative diagnosis did not correlate with the definitive histology of SFT. In patients with the limb location of SFT, no signs of recurrence, nor of distant metastases were seen within the study period. 50% of the post-surgical complications were associated with the abdominal location of the SFT. In newly diagnosed SFT patients, two patients (20%) developed local recurrence, and the median time until recurrence was 22.5 months. Out of patients that were admitted and operated on for recurrent SFT, 67% relapsed and the median time to relapse was 9.5 months. The systemic progression of the disease was observed in 33% of patients treated for recurrent SFT. Conclusion: In our study, the misdiagnosis rate was high and correlated with previously published studies. Post-surgical complications were associated with the extrathoracic location of SFT. The mainstay of SFT treatment remains radical surgery, although radiotherapy alone can significantly improve the overall survival. Clinical trials are urgently needed to evaluate the potential effect of other treatment modalities, such as immunotherapy and targeted therapy, in SFT patients.